Prevalence of T2 Diabetes Mellitus (DM) Among the Rural People of Selected villages Of Bangladesh (Community Based Medical Journal, 2015)
Objectives: This cross-sectional study was conducted to find out the prevalence of type 2 diabetes and pre-diabetes ((PD) (Impaired fasting glucose-IFG, impaired glucose tolerance-IGT)) and to see the associations with risk factors.Methods: Two villages were randomly selected from rural area of Mymensingh district. 125 study subjects (≥30 years) were selected with systematic procedure but 118 samples were participated in the study. Below 30 years, diagnosed case of diabetes and urban people were excluded from study. Socio-demographic data were collected on a pre-tested interview schedule through face to face interview. DM, PD were interpreted by estimating fasting blood glucose level and 2 hour after 75 gm glucose load. Obesity was assigned by BMI. SPSS program (version 11.5) used for data analysis.Results: Mean age of participants was 46.68 with SD ± 12.698. Female participation (66.9%) was double compare to male, literacy rate was (64.4%) with female illiteracy of 29.67%. House wives (61.9%) were more than other professions. Middle class people were nearly 73%, Poor 14.4%, sedentary life style 11% and depressives 14.4% evident in study. A 20.3% people did laborious works. 17.8% had the family history of diabetes. Smokers (53.4%) were more than the non-smokers. Majority (89.0%) of rural people eat rice thrice a day. Normal BMI 61.0%, underweight 31.4% and 7.6% overweight observed.  Overall prevalence of T2 DM was 11.0% showing increase trend of diabetes compared to 8.6% estimated in 2000 and higher than several studies of home and abroad. Female showed higher prevalence (7.6%) compare to male (P>0.05). The overall prevalence of PD was 16.1% evident in this study. The prevalence of IFG and IGT were 8.5% and 7.6% respectively. Female showed higher prevalence of IFG (5.1%) and IGT (5.9%) than male (P>0.05). House wives showed higher prevalence (5.6%) of DM compare to other professions (P>0.05). Illiterates showed more PD (10.3%) and less DM (1.7%) but literates showed more (9.3%) DM (P >0.05). DM (6.7%) and PD (11.8%) more were among the middle class (P=0.018). A high prevalence of PD (13.6%) and DM (9.3%) noticed among non-sedentary lifestyle (P >0.05). Smoker showed higher DM (8.5%) and PD (11.8%). (P-0.071). Prevalence of PD and DM were high among the people with physically less active (P =0.795). Depressives showed more prevalence of DM (8.5%) and PD (13.5%), (P=0.345). increased frequency of rice eating (P=0.004), people with normal BMI (P=0.081) and family history of DM (P=0.000) showed positive association with diabetes mellitus.CBMJ 2015 January: Vol. 04 No. 01 P: 22-29